2003
DOI: 10.1016/s1359-1789(02)00104-0
|View full text |Cite
|
Sign up to set email alerts
|

The heterogeneity of spouse abuse: a review

Abstract: Recent research suggests that spouse abusers are not a homogenous group. Holtzworth-Munroe and Stuart (1994) propose three types of domestic violent men; Family Only, Generally Violent/Antisocial and Dysphoric/ Borderline Personality. This theoretical classification is compared to nine empirical research studies and two hypothetical studies, which can be found in the literature dated from 1994 onwards. The review provides support for the three-fold typology. The total averages of offenders classified by Holtzw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
112
2
10

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(143 citation statements)
references
References 38 publications
19
112
2
10
Order By: Relevance
“…A majority of international IPV studies focuses exclusively on violence against female victims. The main argument is that women suffer more severe consequences and seek help more frequently than male IPV victims (Archer 2000;Campbell 2004;Dixon and Browne 2003;Frye et al 2006). A nationwide survey on domestic violence in Norway found that 10% of the women and 2% of the men had experienced severe IPV (Haaland et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A majority of international IPV studies focuses exclusively on violence against female victims. The main argument is that women suffer more severe consequences and seek help more frequently than male IPV victims (Archer 2000;Campbell 2004;Dixon and Browne 2003;Frye et al 2006). A nationwide survey on domestic violence in Norway found that 10% of the women and 2% of the men had experienced severe IPV (Haaland et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…They tend to have quite conservative attitudes toward women, although this may make them appear similar to jealous Dysphoric-Borderline men. Consistent with the work of Johnson (2006) and Kelly and Johnson (2008), Holtzworth-Munroe and Meehan (2004) show that the violence of "Family Only" batterers tends to be less intentionally controlling and more contextually driven than that of domestic violence perpetrators with antisocial or borderline personality disorders; a finding UK researchers have also replicated (Dixon and Browne 2003). Meanwhile, Stuart et al (2006) provide some support for Kelly and Johnson's claims about the way in which Violent Resistance emerges as a response to Coercive Control.…”
Section: Personality Typesmentioning
confidence: 57%
“…While typologies of violent men provide useful information for professionals working with male perpetrators, researchers have suggested that such typologies provide a narrow focus as they do not consider other important factors that may contribute to the cause and maintenance of IPV, such as the family context and the role that both partners play in the intimate relationship (e.g., Dixon & Browne, 2003). Indeed, it has been stipulated that aggression in the family is a product of the person -environment interaction (Frude, 1991) and therefore a dyadic approach to understanding IPV seems useful.…”
Section: Characteristics Of Couplesmentioning
confidence: 99%